2022
DOI: 10.1021/acsomega.1c05908
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of 3D-Printed Porous Ti6Al4V Scaffolds with a Sr-CaP Coating for Bone Regeneration

Abstract: To improve osseointegration caused by the stressshielding effect and the inert nature of titanium-based alloys, in this work, we successfully constructed a strontium calcium phosphate (Sr-CaP) coating on three-dimensional (3D)-printed Ti6Al4V scaffolds to address this issue. The energy-dispersive X-ray spectroscopy (EDS) and X-ray diffraction (XRD) results indicated that the coatings with and without Sr doping mainly consisted of CaHPO 4 . The bonding strength of Sr doping coating met the required ISO 13 779-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Ti-Sr bound nanotubes can effectively inhibit osteoclast differentiation by inhibiting NF-κB and Akt/NFATc1 pathways, as well as negatively regulating the ERK pathway in vivo and in vitro [ 109 ]. Sr-composited Ti implants accelerated bone healing [ 110 ] and significantly raised macrophage phenotype and anti-inflammatory factor production to enhance bone integration [ 111 ]. Ding et al [ 112 ] prepared protein supramolecular nanofilm (Ti-Ly-Sr) composited with Sr on Ti, cell morphology observation, cell activity assay, ALP staining, and quantitative analysis showed that Ti-Ly-Sr enhanced the early adhesion, proliferation, and osteogenic differentiation of BMSCs, increased the expression of BMSC-related osteogenic genes such as BMP-2, OPG, Runx2, and COL1.…”
Section: Biomaterials Compound With Srmentioning
confidence: 99%
“…Ti-Sr bound nanotubes can effectively inhibit osteoclast differentiation by inhibiting NF-κB and Akt/NFATc1 pathways, as well as negatively regulating the ERK pathway in vivo and in vitro [ 109 ]. Sr-composited Ti implants accelerated bone healing [ 110 ] and significantly raised macrophage phenotype and anti-inflammatory factor production to enhance bone integration [ 111 ]. Ding et al [ 112 ] prepared protein supramolecular nanofilm (Ti-Ly-Sr) composited with Sr on Ti, cell morphology observation, cell activity assay, ALP staining, and quantitative analysis showed that Ti-Ly-Sr enhanced the early adhesion, proliferation, and osteogenic differentiation of BMSCs, increased the expression of BMSC-related osteogenic genes such as BMP-2, OPG, Runx2, and COL1.…”
Section: Biomaterials Compound With Srmentioning
confidence: 99%
“…The XRD and SEM methods revealed that the consolidation of the Thus, this study demonstrates for the first time that volume-printed porous CaSiO 3 -HAp powder with a Ti6Al4V reinforcing matrix has superiority in both bone regeneration potential and mechanical development in the repair of thin-walled bone defects. In this regard, mechanically robust volume CaSiO 3 -HAp powder with a Ti6Al4V reinforcing matrix is promising for certain scenarios of bone defect repair, especially for the repair of thin-walled craniomandibular-facial bone defects [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Su et al [69] successfully addressed the bio-inertness of Ti alloy surfaces by constructing strontium calcium phosphate (Sr-CaP) coatings on 3D-printed Ti6Al4V scaffolds. To address the bio-inertness and poor osteointegration of Ti alloys, Zhang et al [70] explored using CAD combined with 3D printing to reconstruct posterior wall fractures of acetabular fractures, assessing the biomechanical properties of porous Ti alloy scaffolds integrated with steel plates and Ti nitride bio-ceramic coatings.…”
Section: Physical Mechanical Surface Coating Technologymentioning
confidence: 99%